Reconciliation Amongst Islamic-Based Groups as a Solution to the Tolerance Issue and the Accomplishment of Religious Moderation in Indonesia - Haris, Yogi Sopian; Bustam, Betty Mauli Rosa (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
(Salafi) secst in several Indonesian cities reflect a fundamental tolerance problem that endangers harmony and social stability in Indonesia's multicultural society. This study aims to explore ways to bridge differing perspectives on religious tolerance, which can serve as a solid foundation for the development of a peaceful and respectful Indonesian society, as well as to be prepared to encounter future problems of religious tolerance crisis. This research uses a systematic literature review method. Data collection is conducted through the examination of various written sources such as books, scientific articles, research journals, and documents relevant to the research topic. Data analysis is carried out by reviewing, comparing, and integrating information from various bibliographic sources to understand the root of the problem and formulate a comprehensive solution. Findings indicate that Aswaja and Salafi are Indonesia's two primary sects of Islam, with distinct approaches and ideas. Aswaja is more moderate, valuing ijtihad and scientific heritage, whilst Salafi is more literate, condemning heresy and local traditions. Differences in beliefs and convictions, identity politics, extremism, hoaxes, and the lack of tolerance education are factors of conflict between these two streams. Reconciliation efforts can be carried out by integrating local wisdom into interfaith dialogue, involving local figures in education and outreach, fostering collaboration between community-based regions, applying moderation values in social and religious activities, and developing educational programs that are sensitive to local diversity, and involving both the community and the government. The moderation of religious thought is very important in the contemporary era to create harmony and unity, counter extremist ideologies, support interfaith dialogue and social development, maintain the relevance of religious teachings, and promote social integration and diversity.